Nanocomposite of electrochemically reduced graphene oxide and gold nanourchins for electrochemical DNA detection - Mostafa Azimzadeh; Zahra Aghili; Behrooz Jannat; Saeid Jafari; Saeed Rafizadeh Tafti; Navid Nasirizadeh (IET Nanobiotechnology)
Abstract A nanocomposite of graphene oxide and gold nanourchins has been used here to modify the surface of a screen‐printed carbon electrode to enhance the sensitivity of the electrochemical DNA detection system. A specific single‐stranded DNA probe was designed based on the target DNA sequence and was thiolated to be self‐assembled on the surface of the gold nanourchins placed on the modified electrode. Doxorubicin was used as an electrochemical label to detect the DNA hybridisation using differential pulse voltammetry (DPV). The assembling process was confirmed using scanning electron microscopy (SEM) imaging, cyclic voltammetry (CV), and the EIS method. The high sensitivity of the proposed system led to a low detection limit of 0.16 fM and a wide linear range from 0.5 to 950.0 fM. The specificity of the DNA hybridisation and the signalling molecule (haematoxylin) caused very high selectivity towards the target DNA than other non‐specific sequences.